Aging and stress-dependent dielectric properties of multiferroic bismuth ferrite ceramics - M. Unruan (2018)
Dielectric aging and stress-dependent dielectric properties of bismuth ferrite (BFO) and manganese (Mn)-doped bismuth ferrite (BFMO) ceramics were investigated. The dielectric properties of BFO ceramics were decreased significantly with the compressive stress, while the changes were reversed for the BFMO samples. For the aging behavior, the dielectric constant decreased significantly with time in the first two and seven hours for BFO and BFMOs, respectively. After that the lower changes of the dielectric constant with time were observed in all samples. Finally, the aging behavior of the BFO and BFMO ceramics was observed to follow the stretched exponential law. © 2011 Elsevier B.V. All rights reserved.